2019
DOI: 10.1073/pnas.1819031116
|View full text |Cite
|
Sign up to set email alerts
|

Memory and resource tracking drive blue whale migrations

Abstract: In terrestrial systems, the green wave hypothesis posits that migrating animals can enhance foraging opportunities by tracking phenological variation in high-quality forage across space (i.e., “resource waves”). To track resource waves, animals may rely on proximate cues and/or memory of long-term average phenologies. Although there is growing evidence of resource tracking in terrestrial migrants, such drivers remain unevaluated in migratory marine megafauna. Here we present a test of the green wave hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
193
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 198 publications
(220 citation statements)
references
References 84 publications
8
193
0
Order By: Relevance
“…; Abrahms et al. ). Our findings demonstrate that the migratory path of East Australian (E1) humpback whales is associated with the position and character of the East Australian Current inner edge.…”
Section: Discussionmentioning
confidence: 97%
“…; Abrahms et al. ). Our findings demonstrate that the migratory path of East Australian (E1) humpback whales is associated with the position and character of the East Australian Current inner edge.…”
Section: Discussionmentioning
confidence: 97%
“…Yet, it is still unclear whether spatial memory is fundamental to its occurrence (Avgar et al ). For mammals, the only evidence of memory‐based migration has come from zebra (Bracis & Mueller ) and blue whales (Abrahms et al ). Most studies suggest that migratory behaviour could simply emerge from tracking resource waves across large landscapes, where individuals follow cues within their perceptual range that change predictably along seasonal gradients (Avgar et al ; Lendrum et al ; Armstrong et al ; Monteith et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research also has revealed that some animals tend to return to areas previously used even after taking into account the profitability of an area (Wolf et al 2009;Merkle et al 2014); and in some instances, such fidelity can cause individuals to return to areas even if they are less profitable or incur fitness costs (Merkle et al 2015;Sigaud et al 2017). The growing realisation that learning and memory play an important role in movement and habitat selection of animals has brought into question how both memory and environmental variability shape animal ecology (Bracis & Mueller 2017;Abrahms et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the Northeast Pacific, blue whales perform latitudinal migrations between tropical wintering/breeding grounds and productive foraging grounds at higher latitudes in the California Current Ecosystem (CCE) (Bailey et al, ; Ballance, Pitman & Fiedler, ; Irvine et al, ; Mate, Lagerquist, & Calambokidis, ). While in the CCE, blue whales follow the spring and summertime progression of the availability of krill (Abrahms et al, ), their primary prey, and demonstrate temporal synchrony with krill availability (Croll et al ; Fossette et al ). While dynamic distribution data on krill are not available at the requisite spatial and temporal scales of our study, previous studies have shown that blue whale habitat in the CCE can be characterized by a combination of dynamic and static environmental characteristics, such as sea surface temperature, thermocline and seafloor depths and primary productivity (Becker et al, ; Hazen et al, ).…”
Section: Introductionmentioning
confidence: 99%